The Effect Of Instrumental Music Relaxation Techniques To Reduce The Level Of Anxiety Of Pregnancy Women - Anggraini, Dewi; Yunita Ristia, Galuh (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Anxiety during pregnancy can affect the psychological development of the mother and the physical and psychological growth of the baby in the womb. Instrumental Music Therapy is one of the effective distraction techniques and is believed to reduce physiological pain, stress, and anxiety by diverting one's attention. Research Objectives To determine the effect of instrumental music relaxation techniques on reducing anxiety levels of pregnant women in the third trimester. The research method used Quasi-Experimental Design. Sampling technique using Quota Sampling with the number of respondents 20 people. The results of the study before being given instrumental music therapy, all pregnant women felt anxious from mild to severe but after being given instrumental music therapy as many as 35% (7 people) pregnant women did not feel anxious. Conclusion There is an effect of instrumental music relaxation therapy on decreasing the anxiety level of third trimester pregnant women in PMB with a P value = 0.010. Suggestions are expected that health services can provide pregnant women to listen to instrumental music. Health services can provide pregnant women to listen to instrumental music in order to reduce anxiety, especially during the third trimester. Keywords: Pregnant Mother Anxiety, Instrumental Music Therapy, Relaxation Techniques